(untitled) - Axelrod, Herbert O. (Neptune, New Jersey, 1991)
Most swordtails and platies are sold every year than any other genus of livebearing aquarium fish. This book discusses species by species, variety by variety, all of the known forms existing at the present time. The book has illustrated them with outstanding color photographs, including their habitats, and tols precisely where they can be found in Central America, mainly Mexico
Keywords: Fishes